2020
DOI: 10.1097/mog.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

Integration of telemedicine into clinical practice for inflammatory bowel disease

Abstract: Purpose of review In the context of the rising incidence and complexity of inflammatory bowel disease (IBD), telehealth offers new ways to support remote and efficient delivery of healthcare services. The aim of this review is to assess the current status of telehealth services in the management of IBD and challenges to adopting telehealth in clinical practice. Recent findings Different modalities of telehealth such as virtual clinics and remote patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…[4][5][6] Key barriers historically limiting telecare have been regulatory and billing challenges, ensuring privacy and security, liability issues, and licensure and technology challenges. 2,7,8 The coronavirus disease 2019 (COVID-19) pandemic forced an accelerated shift from traditional in-person outpatient visits to telecare to promote social distancing and reduce exposure to vulnerable patients. Although past efforts with smaller populations have shown that telehealth for IBD can be cost-effective and high-quality, little is known about the effect of a systems-wide shift towards telehealth.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Key barriers historically limiting telecare have been regulatory and billing challenges, ensuring privacy and security, liability issues, and licensure and technology challenges. 2,7,8 The coronavirus disease 2019 (COVID-19) pandemic forced an accelerated shift from traditional in-person outpatient visits to telecare to promote social distancing and reduce exposure to vulnerable patients. Although past efforts with smaller populations have shown that telehealth for IBD can be cost-effective and high-quality, little is known about the effect of a systems-wide shift towards telehealth.…”
Section: Introductionmentioning
confidence: 99%
“…From a health systems perspective, accessing hospital-based services is also significantly costlier than ambulatory visits. [13][14][15] The relative spending on pharmaceuticals increased over the 2 decades of this study, accounting for ~20% of total spending in patients with IBD, particularly in younger adults and middle-aged adults with IBD. Although we are unable to directly attribute costs to biologic therapy, it is likely that the relative increase in pharmaceutical health care spending is attributed to biologics.…”
Section: Discussionmentioning
confidence: 96%
“…The last decade has shown increased efforts at implementing telemedicine for adult patients with IBD [ 41 ] as virtual services have the potential to reduce costs associated with managing this disease and increase the availability of specialty care [ 34 ]. Within this population, telemedicine is well-accepted and associated with efficient care delivery [ 41 ], decreased rates of hospitalizations, improved patient quality of life [ 42 ], and increased patient satisfaction, empowerment, and collaboration amongst multidisciplinary providers [ 43 , 44 ].…”
Section: Telemedicine In Pediatric Ibdmentioning
confidence: 99%
“…Although the terms are often used interchangeably, telemedicine refers to the use of information and communication technologies (ICTs) for remote health care delivery (without direct physical contact with the patient) [ 31 ]. In contrast, telehealth employs ICTs in a broader spectrum of clinical activities (e.g., provider-to-provider communications) [ 32 ] as well as non-clinical services (e.g., administrative meetings) [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%